2019
DOI: 10.1177/1729881419870664
|View full text |Cite
|
Sign up to set email alerts
|

A leader–follower formation control approach for target hunting by multiple autonomous underwater vehicle in three-dimensional underwater environments

Abstract: As one of the challenging tasks of multiple autonomous underwater vehicles systems, the realization of target hunting is the great significance. The multiple autonomous underwater vehicle target hunting is studied in this article. In some research, because the hunting members cannot reach the hunting point at the same time, the hunting time is long or the target escapes. To improve the efficiency of the target hunting, the leader–follower formation algorithm is introduced. Firstly, the task is assigned based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For target hunting in UIS, if local control approach is directly employed, more hunter agents will be crowded by executing the same behavior, which can cause behavioral aggregation in tracking and capturing process. Furthermore, some early experiments have reported that swarm size should not be too large, it is easy to induce resource waste and computing explosions [4], [6], [20], [22], [25], [41]. Hence, a behavioralintensity control strategy which is inspired by clonal selection theory, is developed to flexibly determine which intensity value is maintained.…”
Section: ) Behavioral-intensity Control Strategy For Behavior Aggregmentioning
confidence: 99%
See 1 more Smart Citation
“…For target hunting in UIS, if local control approach is directly employed, more hunter agents will be crowded by executing the same behavior, which can cause behavioral aggregation in tracking and capturing process. Furthermore, some early experiments have reported that swarm size should not be too large, it is easy to induce resource waste and computing explosions [4], [6], [20], [22], [25], [41]. Hence, a behavioralintensity control strategy which is inspired by clonal selection theory, is developed to flexibly determine which intensity value is maintained.…”
Section: ) Behavioral-intensity Control Strategy For Behavior Aggregmentioning
confidence: 99%
“…Although this method is effective, behavior exploration does not avoid in a particular situation where illegal behavior is evaluated due to the fact that one hunter exists more than one direction to move. Cao and Guo [6] developed a leaderfollower formation algorithm to assign hunting tasks by multiple autonomous underwater vehicles, and an angle matching strategy was utilized to guide round up target by leading hunter, however its topology is rigid to describe the position of agents, which can cause imperfect robustness, especially for large-scale agents. In the aforementioned works, centralized approaches are capable of achieving target hunting, however drawbacks cannot be ignored in dramatically changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Five AUVs are distributed in the 3D underwater environment, their original positions are (7,45,18), (9,28,5), (19,9,3), (4,45,14), and (27,49,46). They are represented by dots in different colors.…”
Section: A Target Hunting When Auv Is the Same Velocity As The Targetmentioning
confidence: 99%
“…The AUVs complete the hunting at the target marching point (32,38,37). Under the same conditions, the proposed algorithm uses five AUVs to successfully close the target at (28,25,22), and the hunting distance is shortened by 48%, as shown in Figure 9(b). By analyzing the reasons, it can be seen that the path selection of AUV hunting in a bioinspired neural network algorithm adopts the trajectory tracking strategy, and AUV always follows the target.…”
Section: Figure 8 the Structure Diagram Of Bio-inspired Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation